A developmental perspective on marital closeness and health in older adulthood. (August 2019) - Burke, Leah K.; Rauer, Amy; Sabey, Allen K.
Although closeness is a necessary element in relationships, its role in later-life marriages is less clear, with some finding benefits of greater closeness and others finding costs. To begin to reconcile these findings, the current study sought to explore older couples' experiences of both desired and actual closeness over time. Drawing upon both socioemotional selectivity theory and the dynamic goal theory of marital satisfaction, the current study examined the stability of marital closeness among older couples and the role of health in shaping both within-spouse and cross-spouse associations. We utilized a series of cross-lagged, mutual influence, actor–partner interdependence models to examine how higher-functioning older couples' ( N T1 = 64, N T2 = 55) actual and desired marital closeness were linked over a year and whether subjective and objective health moderated these pathways. Findings revealed that older spouses reported enjoying and desiring close relationships within their marriages, but these feelings of and desire for closeness were more stable for husbands. Moderational analyses, however, indicated that the desire for and experience of closeness were sensitive to spouses' health. These findings suggest that both gender and health may be important considerations when understanding the stability of and cross-partner associations in marital closeness for older couples.